Is the Active Approach to Labour Market Policy Effective? - Laurisz, Norbert (Journal of Public Governance, 2018)
The article presents a reflection on the effectiveness of an active labor market policy. The analysis was inspired by various international empirical studies in the field of ALMP. The main objective of the study was to describe the direction of changes in labor market policies - the transition from the ‘welfare state’ to the ‘welfare to work’ approach. Secondly, the author wanted to describe the methods of implementation of ALMPs in the EU countries. Finally, the article is also an attempt to determine precisely the effects of the implemented active labor market policies – their positive and/or negative impact on the labor market.